Pentingnya literasi keuangan bagi ibu rumah tangga di Dusun Karanjang Kota Ambon - Anwar, Arman; Paeng, Raju; Usirin, Fadly Febriyan (STAI Auliaurrasyidin Tembilahan, 2024)
Financial literacy is essential, particularly for housewives who manage household finances. A lack of understanding in this area can hinder wise financial decision-making. This study aims to enhance the financial literacy of housewives in Dusun Karanjang, Desa Wayame, Kota Ambon. The program employed a community education approach, including financial planning training, financial health assessments, and interactive discussions. The results indicated improvements in participants' abilities to manage budgets, save, and assess financial health, positively impacting family welfare. Challenges such as limited resources and time were addressed through recommendations for continuous mentoring and financial simulations. This program is expected to enhance financial literacy, promote economic stability within families, and contribute to overall community well-being.